Penyusunan Material Produk Hand Craft di Home Industry - Arista, Anggia; Tipa, Handra (Fakultas Teknik UMRI, 2024)
Goods storage is very important in every business. Having proper, good storage will make it easier for a business to run its business. However, storage of goods will not be effective if the arrangement of goods is not arranged properly. Hand craft products are businesses engaged in the field of handicrafts that produce several products such as: plaques, house numbers, key chains, acrylic boxes which are produced on a large scale, for this reason product classification is needed to make it easier for workers in this business. The ABC classification method is the most effective method, dividing items into classes and assigning to each class a set of areas in which the product belongs. From the research results, group A was obtained, namely plaques, name plates and key chains, while group B was acrylic house numbers, anchors, character wall clocks, and acrylic motorbike plates and group C was acrylic boxes, where group A was preferred.